Case Report: Utility of brain [18F]FDG PET/CT in the diagnosis of Sydenham's chorea - Dambrain, Abel; Boursot, Charles; Cohen Tannugi, Kévin; Reichart, Julien; Lacoeuille, Franck (Frontiers in Nuclear Medicine, 2024)
Sydenham's chorea is an autoimmune reaction against cerebral basal ganglia associated with rheumatic fever, caused by group A beta-hemolytic streptococcus infection. Diagnosis of this condition is difficult because of significant delay between infection onset and symptoms presentation, resulting in few positive biological tests or imaging exams. We report the case of a nine-year-old boy exhibiting hemicorporal abnormal movements with tics for whom [18F]FDG PET/CT exam allowed to make the diagnosis, associated with anti-DNase B elevation. Other biology, spinal tap, EEG and imaging modality like MRI or scanner, were non-contributory.